Family firms, corporate governance and firm performance : in Singapore context - Lim, Wan Zhen (Nanyang Technological University, 2009)
In this paper, we aim to investigate the relationship between family-managed firms and their performance. Using the proportion of family members on the board of directors and return on equity (ROE) as the performance indicator, our group ran a regression to find out their correlation and more importantly, how the quality of corporate governance moderates the relationship. We collected data on 412 firms from the Singapore Stock Exchange to carry out our investigation. From the results, we discovered that there is a positive correlation between the proportion of family members on the board of directors and the firm‘s performance. We also found that the proportion of equity held by inside directors (excluding CEO), the proportion of equity held by CEO and the proportion of equity held by outside directors have significant moderating effects.